The relation between college students’ neuroticism and loneliness: The chain mediating roles of self-efficacy, social avoidance and distress - Li, Shuna; Kong, Kaizhen; Zhang, Kaijie; Niu, Hua (Frontiers in Psychology, 2023)
Recently, identifying the psychological mechanism of college students' loneliness has attracted wide attention because the maladjustment caused by college students' loneliness is increasingly common. This study explored the relationship and potential mechanism between college students' neuroticism and loneliness in a large sample. A total of 4,600 college students completed the Big Five Personality Scale, Loneliness Scale, Self-efficacy Scale and Social Avoidance and Distress Scale. By examining the chain mediating roles of self-efficacy, social avoidance and distress (SAD) in the relation between neuroticism and loneliness, the present study found that college students' neuroticism was positively associated with loneliness via self-efficacy and SAD, respectively, and sequentially. The results of this study have important implications for revealing the influencing factors of loneliness among college students and improving the methods to alleviate loneliness among them.